Allied contributions in support of Operations Desert Shield and Desert Storm : statement of Frank C. Conahan, Assistant Comptroller General, National Security and International Affairs Division, before the Committee on Ways and Means, House of Representatives / United States General Accounting Office. (1991)
Summary goes here